2001
DOI: 10.1063/1.1385576
|View full text |Cite
|
Sign up to set email alerts
|

Influence of dose rate on bubble formation by high energy He implantation in silicon

Abstract: Articles you may be interested inEffect of implant temperature on defects created using high fluence of helium in silicon Strain development and damage accumulation during neon ion implantation into silicon at elevated temperatures Boron segregation to extended defects induced by self-ion implantation into silicon

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 28 publications
1
8
0
Order By: Relevance
“…In theory, combining these experiments could allow following the structural and chemical evolution of the bubbles. However, as the implantation conditions [32][33][34] and the annealing procedure [35][36][37] play a crucial role in the bubble formation and evolution, the relevance of a comparison between different experiments is seriously limited.…”
Section: Introductionmentioning
confidence: 99%
“…In theory, combining these experiments could allow following the structural and chemical evolution of the bubbles. However, as the implantation conditions [32][33][34] and the annealing procedure [35][36][37] play a crucial role in the bubble formation and evolution, the relevance of a comparison between different experiments is seriously limited.…”
Section: Introductionmentioning
confidence: 99%
“…The beam flux was kept in the range of ͑3-6͒ ϫ 10 12 ions cm −2 s −1 , since it was shown that changes in the implantation flux can strongly affect the accumulation of defects. 35,42 Some implantations were carried out at room temperature while others were performed at temperatures ranging from 100 up to 600°C to avoid target amorphization. Anneals were performed in a vacuum of ϳ10 −7 torr at temperatures ranging from 400 to 1100°C for 30 min in a quartz tube within a tubular furnace.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…Such planetarylike clusters are observed during conventional annealing for temperatures higher than 400°C. 10,22,23 These different evolutions appear only for annealing temperatures higher than a critical temperature pointing out the diffusion and H-gettering by the He-plates, so favoring its bi-dimensional growth. These observations agree with dynamical simulations as well as experiments conducted on the disk-shaped defects involving H, for which their growth is controlled by a subcritical stress-corrosion mechanism.…”
Section: Resultsmentioning
confidence: 99%